Szczyt kościoła Najświętszej Marii Panny na Ostrowie Tumskim w Poznaniu. Budowa, ikonografia, źródła archeologiczne - Antowska-Gorączniak, Olga (Ecclesia. Studia z Dziejów Wielkopolski, 2013)
The article describes one of the elements of the gothic church of the Blessed Virgin Mary at Ostrów Tumski in Poznań - its western gable. It is a crow-stepped construction with twelve pinnacles with floriated terminations and a younger ave-bell. The present forms ceramic pinnacles and fleurons come from the extensive redecoration that the church underwent in mid-19th century, as testified by the dates carved on their underside (1859 - illustration 3) and the surviving bills. From older iconography (F.B. Werner 1734; J. Minutoli 1833; K.W. Kielisiński - the 1840s) it is evident that the church also in earlier times had pinnacles, probably gothic ones. It is assumed that the construction of the church was begun by builders from West Pomerania ca. 1430 r., and the edifice was completed by the local stonemasons. From written sources it follows that the gable of the church was erected in 1445 by Lorko of Kościan. It can be supposed that the gothic pinnacles were executed by the local Greater Poland craftsmen.